2012
DOI: 10.1371/journal.pone.0045766
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani Triose Phosphate Isomerase: A Potential Vaccine Target against Visceral Leishmaniasis

Abstract: Visceral leishmaniasis (VL) is one of the most important parasitic diseases with approximately 350 million people at risk. Due to the non availability of an ideal drug, development of a safe, effective, and affordable vaccine could be a solution for control and prevention of this disease. In this study, a potential Th1 stimulatory protein- Triose phosphate isomerase (TPI), a glycolytic enzyme, identified through proteomics from a fraction of Leishmania donovani soluble antigen ranging from 89.9–97.1 kDa, was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 65 publications
0
26
0
Order By: Relevance
“…Previously, the selection of antigens for developing vaccines has predominantly focused on extracellular protein targets, on the premise that intracellular proteins are not accessible to antibodies. However, there is ample evidence suggesting that intracellular proteins might be useful targets for vaccination against ticks and other parasites (Parizi et al, 2011;Balaban et al, 1995;Kushawaha et al, 2012). Taken together, these results indicate that CDKs are suitable targets for designing vaccines against for Ixodes tick species.…”
Section: Discussionmentioning
confidence: 87%
“…Previously, the selection of antigens for developing vaccines has predominantly focused on extracellular protein targets, on the premise that intracellular proteins are not accessible to antibodies. However, there is ample evidence suggesting that intracellular proteins might be useful targets for vaccination against ticks and other parasites (Parizi et al, 2011;Balaban et al, 1995;Kushawaha et al, 2012). Taken together, these results indicate that CDKs are suitable targets for designing vaccines against for Ixodes tick species.…”
Section: Discussionmentioning
confidence: 87%
“…Kushawaha et al (48, 50, 51) studied the immunogenicity of LelF-2, TPI, and PDI of L. donovani in PBMCs of cured Leishmania -infected patients and hamsters where they found Thl-type cytokine profile (production of IFN-γ, IL-12, and TNF-α but not IL-4 or IL-10) with a remarkable increase in IgG2 and considerable protection. Gupta et al (49, 53) reported p45, enolase, and aldolase as a potential vaccine candidate with considerable prophylactic efficacy to the tune of 85–90% with an increased mRNA expression of iNOS, IFN-γ, TNF-α, and IL-12 and decrease in TGF-β and IL-4.…”
Section: Molecular Approaches To Leishmania Vaccine Developmentmentioning
confidence: 99%
“…Accordingly, PCR methods have been widely used to detect Leishmania infection in clinical specimens with a high sensitivity and specificity [13]. Several PCR approaches have been published based on different target genes, i.e., the cysteine protease B (cpb) [14], the cytochrome b (cyt b) [15], the internal transcribed spacer 1 (ITS1) region of the small subunit ribosomal RNA (SSU-rRNA) gene [16], the glucose-6-phosphate dehydrogenase (G6PD) [17], the heat shock protein 70 (hsp70) [18], the spliced leader mini-exon [19], the SSU-rRNA gene [20] and the triose-phosphate isomerase (tim) genes [21]. Of these, the ITS1 region of the SSU-rRNA gene has been one of the common genetic markers used to detect Leishmania species in the Old World [13,16,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%